Assessing differences among elasmobranch nurseries to aid conservation based on a genomics framework - Dominic G. Swift; Amanda M. Barker; William B. Driggers; Bryan S. Frazier; Douglas H. Adams; James J. Gelsleichter; Dana M. Bethea; Bethany M. Deacy; David S. Portnoy (Conservation Biology, 2026)
Elasmobranch nurseries often differ in environmental conditions, demographics, and use patterns. These differences affect the distribution of genetic variation among nurseries. However, conservation and management strategies often fail to account for such differences because they are difficult to characterize. We assessed differences in connectivity, genetic variation, and numbers of breeders among scalloped hammerheads ( Sphyrna lewini ) sampled in five nurseries in the western North Atlantic Ocean. We used a reduced‐representation genomic approach to genotype 472 young of the year and small juveniles at 8,334 loci containing single‐nucleotide polymorphisms. We inferred full‐ and half‐sibling relationships and used mitochondrial genome haplotypes to differentiate between maternally and paternally related half‐siblings. Among 45 sibling pairs detected, 91% were from the same nurseries and only four pairs were sampled in different nurseries, indicating strong site fidelity. Weak but significant genetic heterogeneity was detected among nurseries based on analysis of molecular variance (0.02% variation, F ST 0.00018, 95% confidence interval 0.00008–0.00028). We quantified standing genetic variation and estimated the contemporary effective population size for each nursery, and although some differences were observed, they were not statistically significant. Our results suggested that female scalloped hammerheads consistently used specific nurseries and that connectivity (via males or females straying between nurseries) facilitated the dispersal of genetic variation, which may enhance population resilience to environmental change. The genomics framework we applied is broadly applicable to conservation‐based assessments of elasmobranch nurseries and essential habitats of other highly mobile species and provides a powerful tool for addressing conservation challenges.